(untitled) (Journal of International Studies, 2020)
The conduct of intra-Commonwealth "consular relations " prior to the 1963 Vienna Convention on Consular Relations was unique in that the relations were dissimilar to that established between foreign states. The former had traditionally conducted theirs on a "host" convention, and with the assistance of British missions. The codification of the VCCR,which introduced an element of uniformity of consular rules and procedures, had posed a challenge to intra-Commonwealth quasiconsular practices. This came in a most difficult period in the Commonwealth relations - in what Harold Macmillan described as the "wind of change" that proved to be uncomfortable for Her Majesty’s Government, not to mention Britain ’s application to join the European Economic Community. The paper examines the impact of the VCCR on the Commonwealth’s long-standing arrangement in consular relations. It looks at the British Government’s efforts, vis-a-vis, the Commonwealth Relations Office to maintain the status quo and the factors that had influenced some member states to look towards formalising their consular relations. This desire to move away from the traditional norm indicated the coming of age of member states: to determine the direction of their governments’ foreign affairs machinery rather than to be free from the vestiges of the British heritage. The paper also looks at why, after nine years, member states finally got together to address this issue and the implication of the 1972 London Conference on the Commonwealth’s consular practices.